"Go Faster!": Adults' Essentialist Representation of Gender and National Identity, but Not Race, Is Revealed by Cognitive Demand. Issue 1 (1st January 2022) - Siddiqui, Hasan; Rutherford, M.D.
ABSTRACT: Essentialism is the intuition that category membership relies on an invisible essence. Essentialist thinking about social categories is most evident in young children, while comparable methods do not reveal essentialist thinking about social groups in adult participants. However, previous work has found that essentialist thinking about gender was measurable in adults who experienced cognitive demand. In this paper, we studied essentialist intuitions about national identity, race, and gender, in adults under cognitive demand. We found that adults under cognitive demand essentialized national identity and gender more than adults who had time to deliberate, though cognitive demand had no effect on essentialist intuitions about race. Additionally, we found evidence that adults' essentialist intuitions were strongest for gender, followed by race, and then national identity. The asymmetry in essentialism levels across the three studies suggests that there may be different mental representations for different social categories.